First report of the presence of L1014S Knockdown-resistance mutation in Anopheles gambiae s.s and Anopheles coluzzii from Togo, West Africa - Djegbe, I.; Akoton, R.; Tchigossou, G.; Ahadji-Dabla, K.M.; Atoyebi, S.M.; Adeoti, R.; Zeukeng, F.; Ketoh, G.K.; Djouaka, R. (F1000 Research Ltd, 2018)
Background: To optimize the success of insecticide-based malaria control intervention, knowledge of the distribution of Anopheles gambiae species and insecticide resistance mechanisms is necessary. This paper reported an updated data on pyrethroids/DDT resistance in the An. gambiae s.l population from Togo.